A Sticky Situation: Poor Correlation Between Platelet Inhibition Assays. (11th September 2019) - Dean, Christina L; Duncan, Alexander; Ingle, Ann; Guarner, Jeannette; Roback, John D; Sullivan, Harold C; Maier, Cheryl
Abstract: Monitoring antiplatelet therapy is critical in patients undergoing cardiac or neurologic stent placement to ensure adequate platelet suppression and prevent thrombosis. Light transmission aggregometry (LTA) using platelet-rich plasma (PRP) is the gold standard to assess platelet responsiveness to aspirin (ASA) and P2Y12 inhibitors (P2Y12-I). Other platforms for antiplatelet therapy monitoring employ whole-blood aggregometry (WBA) via electrical impedance (EA) or ELISA-based detection of urinary metabolites. The goal of this study was to evaluate the concordance of four antiplatelet therapy monitoring platforms. Blood and urine samples from 20 patients receiving antiplatelet therapy prior to neurologic stent placement were prospectively collected. Blood samples were analyzed by LTA using PRP on the Helena AggRAM and by WBA-EA using the Chrono-log Lumi-aggregometer to assess ASA and P2Y12-I response. For the LTA, the maximum amplitude (MA) of the platelet aggregation curve was determined using high-dose (HD) and low-dose (LD) ADP agonist for measuring P2Y12-I response and with arachidonic acid (AA) for ASA response. For the WBA, resistance (ohms) was measured with ADP for P2Y12-I response and with HD and LD collagen for ASA response. Whole-blood samples were also analyzed with the VerifyNow PRUTest to assess platelet response to P2Y12-I. Urine samples were analyzed with AspirinWorks. Concordance of antiplatelet response based on predefined cutoff values (eg, concordant = optimal/optimal, discordant = optimal/suboptimal), as well as correlation between actual units of measure, was determined. When comparing P2Y12-I response determined by LTA and WBA, overall concordance was 55% (correlation was r = 0.75 and 0.65 for HD and LD ADP, respectively). VerifyNow was concordant with LTA in 70% ( r = 0.86 and 0.75 for HD and LD ADP, respectively) and with WBA in 45% ( r = 0.57) of samples. When comparing ASA response between LTA and WBA, overall concordance was 70% ( r = 0.09 and 0.19 for HD and LD collagen, respectively). AspirinWorks was concordant with LTA and WBA in 60% of samples ( r = 0.32 for LTA; r = 0.08 LD collagen, r = 0.02 for HD collagen on WBA). In summary, concordance varied between 45% and 70% on the four antiplatelet therapy monitoring platforms. Testing of P2Y12 inhibition showed the best correlation between LTA HD ADP and VerifyNow ( r = 0.86). When comparing WBA vs LTA, the strongest correlation was between LD ADP LTA and WBA ( r = 0.75). Correlation with ASA inhibition was overall poor between the various assays ( r ranging between 0.02 and 0.58). The results from this correlation study support the continued use of LTA with HD and LD ADP and AA; other testing methods can be used as adjuncts when LTA proves difficult to interpret.